Profil Health-Related Quality of Life (HRQOL) Masyarakat Surabaya - Dewi Perwito Sari; Digdo Suryagama (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
The development of a nation or state is determined by one of the factors, namely socially and economically productive human resources. Productive human resources are part of the health development plan that has been planned by the Ministry of Health of the Republic of Indonesia through the 2015-2019 Strategic Plan. Improving the quality of human life where health-related quality of life (HRQoL) is part of the main strategic plan. A large and healthy population of productive age supports the wheels of a country's development. Surabaya is one of the metropolitan cities with an estimated productive age population of 75.86% in 2019. This study aims to describe the HRQoL of the people of Surabaya City in 2019. This study is survey research conducted in a descriptive cross-sectional manner using a survey sheet (questionnaire) SF6D in Indonesian version that has been validated. Quality of life assessment is expressed in utility values and analyzed by correlation test and difference test. The results of a survey conducted on 226 people resulted in an average utility score of 0.8945 with an SD of 0.1109. Significant differences can be seen in the utility values of the age, education, and marital status groups (p<0.05). The results of the study concluded that the HRQoL of productive age in Surabaya was good, while the factors of age, education, and status influenced the level of HRQoL